2019
DOI: 10.1029/2019gc008453
|View full text |Cite
|
Sign up to set email alerts
|

Geochemistry of Fluid Inclusions in Travertines From Western and Northern Turkey: Inferences on the Role of Active Faults in Fluids Circulation

Abstract: The understanding of the relationship between the geochemistry of fluids circulating during travertine deposition and the presence of active faults is crucial for evaluating the seismogenetic potential of an area. Here we investigate travertines from Pamukkale and Reşadiye (Turkey), sited in seismic regions and next to thermal springs. These travertines formed ~24,500–50,000 (Pamukkale) and ~240–14,600 years (Reşadiye) BP. We characterize fluid inclusions (FIs) and studied concentration of H2O, CO2, O2 + N2, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 100 publications
0
6
0
Order By: Relevance
“…The remarkable heterogeneous crystallisation indicates that the continuous fluid flow with high discharge rate resulted in carbonate deposition in a turbulent environment (e.g. Rizzo et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The remarkable heterogeneous crystallisation indicates that the continuous fluid flow with high discharge rate resulted in carbonate deposition in a turbulent environment (e.g. Rizzo et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Noble gases are investigated in fluid inclusions occurring in a variety of minerals, e.g., in olivine, pyroxene, amphibole, sulphides, or basaltic glasses; these are of interest when questions about magma origins and mantle contributions are Crustal rock studies (48) Climate studies (9) Deep water studies (4) Mantle rock studies (49) Method studies (7) Ore studies (45) Extraterrestrial rocks studies (3) TWO CRUSHER 3 Geofluids investigated. Studies of crustal composition and origin have analysed fluid inclusions found in olivine, calcite, fluorite, eclogite, corundum, quartz, or whole rock pieces (e.g., [58][59][60][61]). Common minerals relevant for noble gas analyses in fluid inclusions for ore studies are ore-associated minerals like quartz, pyrite, calcite, or fluorite (e.g., [3,40,53,62]).…”
Section: Fluid Inclusion Genesismentioning
confidence: 99%
“…Another crusher uses single-step systems with a stainless-steel bowl in ultrahigh vacuum conditions which can apply up to 2000 bar pressure [98]. This crushing system is capable to process six samples simultaneously [61,100,101]. [99,102] used a combination of a 1 cm diameter and a 6 to 10 cm long stainless-steel sampler, a hydraulic piston with applied pressure up to 200 bar, and a stainless-steel plate (AISI 316 LRN) placed below the sampler.…”
Section: Milling and Shakingmentioning
confidence: 99%
“…The results suggest that the events recorded in Ca-carbonate veins indicate an epicenter with a distance of <200 km and high-intensity (I > VI) paleoearthquakes; thus, this tool has advantages over traditional paleoseismological methods for the understanding of long-term earthquake behavior. In this view, it should be possible to use age determination to reconstruct the seismicity and its recurrence [23,65,100], the fault dilatation rate [82], the age of a fault [36,65,112,116], an assessment of the slip rate [124], and relationships between faulting and fluid properties in geothermal fields [2,13,35,86,94,132,[151][152][153][154].…”
Section: Advantages Of Using Fissure Ridges For Neotectonic and Seism...mentioning
confidence: 99%